Comparison of Point-of-Care versus Central Laboratory Testing of Electrolytes, Hemoglobin, and Bilirubin in Neonates - Choi, Ha-young; Corder, William; Tefera, Eshetu; Abubakar, Kabir M. (American Journal of Perinatology, 2021)
Objective Electrolyte, hemoglobin, and bilirubin values are routinely reported with point-of-care (POC) testing for blood gases. Results are rapidly available and require a small blood volume. Yet, these results are underutilized due to noted discrepancies between central laboratory (CL) and POC testing. The study aimed to determine the correlation between POC and CL measurement of electrolytes, hemoglobin, and bilirubin in neonates.Study Design Electrolyte, hemoglobin, and bilirubin results obtained from capillary blood over a 4-month period were analyzed. Each CL value was matched with a POC value from the same sample or another sample less than 1-hour apart. Agreement was determined by measuring the mean difference (MD) between paired samples with 95% limits of agreement (LOA) and Lin's concordance correlation (LCC).Results There were 355-paired sodium/potassium, 139 paired hemoglobin, and 197 paired bilirubin values analyzed. POC sodium values were lower (133.5 ± 5.8 mmol/L) than CL (140.2 ± 5.8 mmol/L), p <0.00001 with poor agreement (LCC = 0.49; MD = 6.7; 95% LOA: −13.6 to 0.14). POC potassium values were lower (4.6 ± 0.98 mmol/L) than CL (4.98 ± 1.24mEq/L), p < 0.0001, but with better concordance and agreement. (LCC = 0.6; MD = 0.4; 95% LOA: −2.3 to 1.4). There were no differences in hemoglobin between POC (14.3 ± 3.2 g/dL) and CL (14.4 ± 3.1 g/dL), p = 0.2 with good LCC (0.93) and in bilirubin values between POC (6.0 ± 3.2 mg/dL) and CL (5.8 ± 3.0 mg/dL), MD = 0.18, and p = 0.07.Conclusion POC Sodium values are lower than CL. POC potassium levels are also lower, but the differences may not be clinically important while hemoglobin and bilirubin levels are similar between POC and CL. As POC potassium, hemoglobin, and bilirubin levels closely reflect CL values, these results can be relied upon to make clinical judgments in neonates.Key Points
Keywords: electrolytes; sodium; potassium; hemoglobin; bilirubin; point of care; neonatal intensive care